Modelling the effects of tool edge radius on micro machining based on smooth particle hydrodynamics simulation method. (1st January 2014) - Guo, Xiaoguang; Zhang, Xiaoji; Liu, Ziyuan; Zhang, Dongxiao; Jin, Zhuji; Guo, Dongming
Smooth particle hydrodynamics (SPH) method is introduced to simulate the oxygen-free copper micro-cutting process. At the same cutting thickness r, several different a / r are employed to investigate the effects of tool edge radius on the micromachining mechanism. The simulation results indicate that the larger a / r was, the greater the transverse cutting force was, the smaller the vertical pressure was, which benefits for material removal and good quality surface generation. And it could also be found that the cutting heat was smaller with the smaller a / r, the flows along the rake face generated a large amount of friction heat and oxygen came into the contact slit easily, which caused chemical corrosion on diamond rake face seriously. When the a / r was bigger, chemical corrosion becomes difficult because the cutting tool contacted the material adequately and oxygen was difficult to enter the contact zone.